Світ поетичного слова В. Голобородька-сюрреаліста - Беценко, Т. (Слово і Час, 2018)
У статті розглянуто ознаки поетичної мови В. Голобородька як митця-сюрреаліста.
Виявлено такі риси стильової манери художника слова: мовно-поетична естетизація предметів
і явищ повсякдення; оригінальність, незвичність комбінацій слів; екстраординарність
мовного оформлення поетичної думки; використання прийому творення поетичного дива;
надметафоричність висловлення; трансформація фольклорно-пісенних образів, їх семантичне
ускладнення; поповнення поетично-образної системи новими мовно-естетичними знаками;
поетична алогічність, парадоксальність художнього мовопростору письменника. The paper attempts to consider peculiarities of the poetic language of Vasyl Holoborodko as a
surrealist poet. The following style features of the poet have been revealed: cultural and poetic
aesthetics applied to everyday objects and occurrences; unusual combinations of words for the
purpose of creating poetic linguistic structures; extraordinary linguistic design of the poetic thought;
the method of a poetic miracle; excessively metaphoric character of the poetic expression; multi-stage
figurative meaning of the utterance; complex associativity; transformation of folklore-song images,
their semantic complication; expansion of combinatory ability of words; contextual semantic and
aesthetic arrangement; enrichment, replenishment of the poetic image system with new cultural and
aesthetic signs, rethinking of traditional concepts; poetic illogicality, paradox of poetical language
space.
V. Holoborodko formed a very unusual and individual poetic world; united the folkloric traditions
of the figurative designation of reality with modern linguistic reality. The literary picture of the world
reflected in the poetic discourse of the surrealist is associated with a miracle. The aesthetics of the
writer’s poetic word is solemnly exalted, majestic and fabulous, often extravagant in a peculiar manner.
The style of Vasyl Holoborodko is a reflection of the poetic experience of the artist himself and
the national and world poetic tradition. At the same time, it is a fact of original artistic thinking. The
writer showed the originality of figurative encoding of thought and at the same time demonstrated the
possibilities of his native language in creating a new system of poetic universals. В статье рассмотрены признаки поэтического языка
В. Голобородько как художника-сюрреалиста. Выявлены следующие
черты стилевой манеры художника слова: культурно-поэтическая
эстетизация предметов и явлений повседневности; оригинальность,
необычность комбинаций слов; экстраординарность, языкового
оформления поэтической мысли; использование приема создания
поэтического чуда; сферхметафоричность высказывания;
трансформация фольклорно-песенных образов, их семантическое
осложнение; пополнение поэтической образной системы
новыми культурно-эстетическими знаками; поэтическая
алогичность, парадоксальность художественного языкового
пространства.